Increased Methyl-CpG-Binding Domain Protein 2 Promotes Cigarette Smoke-Induced Pulmonary Hypertension - Wu, Jixing; Huang, Qian; Li, Qinghai; Gu, Yiya; Zhan, Yuan; Wang, Ting; Chen, Jinkun; Zeng, Zhilin; Lv, Yongman; Zhao, Jianping; Xia, Jie; Xie, Jungang (Frontiers in Oncology, 2022)
Pulmonary hypertension (PH) is a chronic vascular proliferative disorder. While cigarette smoke (CS) plays a vital part in PH related to chronic obstructive pulmonary disease (COPD). Methyl-CpG-Binding Domain Protein 2 (MBD2) has been linked to multiple proliferative diseases. However, the specific mechanisms of MBD2 in CS-induced PH remain to be elucidated. Herein, the differential expression of MBD2 was tested between the controls and the PH patients’ pulmonary arteries, CS-exposed rat models’ pulmonary arteries, and primary human pulmonary artery smooth muscle cells (HPASMCs) following cigarette smoke extract (CSE) stimulation. As a result, PH patients and CS-induced rats and HPASMCs showed an increase in MBD2 protein expression compared with the controls. Then, MBD2 silencing was used to investigate the function of MBD2 on CSE-induced HPASMCs’ proliferation, migration, and cell cycle progression. As a consequence, CSE could induce HPASMCs’ increased proliferation and migration, and cell cycle transition, which were suppressed by MBD2 interference. Furthermore, RNA-seq, ChIP-qPCR, and MassARRAY were conducted to find out the downstream mechanisms of MBD2 for CS-induced pulmonary vascular remodeling. Subsequently, RNA-seq revealed MBD2 might affect the transcription of BMP2 gene, which furtherly altered the expression of BMP2 protein. ChIP-qPCR demonstrated MBD2 could bind BMP2’s promotor. MassARRAY indicated that MBD2 itself could not directly affect DNA methylation. In sum, our results indicate that increased MBD2 expression promotes CS-induced pulmonary vascular remodeling. The fundamental mechanisms may be that MBD2 can bind BMP2’s promoter and downregulate its expression. Thus, MBD2 may promote the occurrence of the CS-induced PH.